Leadership Commitment and Internal Control Effectiveness in Financial Reporting: The Mediating Role of the Government Internal Control System in Indonesia's Defense Institutions - Dody Hananto; Andriansyah (Vokatek: Jurnal Pengabdian Masyarakat, 2026)
Increasing demands for transparency and accountability in public financial management have heightened the importance of effective internal control systems, particularly within defense institutions that operate under complex bureaucratic and military command structures. This study aimed to examine the direct effect of leadership commitment on financial reporting quality, investigate the mediating role of the Government Internal Control System (Sistem Pengendalian Intern Pemerintah—SPIP), and compare its implementation within the Indonesian Ministry of Defense and the Indonesian National Armed Forces. An explanatory sequential mixed-methods design was employed by integrating quantitative and qualitative approaches. Quantitative data were collected from 120 financial management personnel through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The qualitative phase involved semi-structured interviews with eight key informants to explain the quantitative findings and explore institutional differences in SPIP implementation. The results revealed that leadership commitment had a positive and significant effect on both SPIP implementation (β = 0.645, p < .001) and financial reporting quality (β = 0.412, p = .002). SPIP also had a significant positive effect on financial reporting quality (β = 0.528, p < .001) and partially mediated the relationship between leadership commitment and financial reporting quality. Qualitative findings further demonstrated that the Ministry of Defense primarily adopted a rule-based administrative approach, whereas the Indonesian National Armed Forces emphasized command-based implementation. These findings suggest that strengthening financial accountability in the defense sector requires an adaptive internal control model that integrates administrative compliance with hierarchical command practices.